2014
DOI: 10.1163/15685381-00002958
|View full text |Cite
|
Sign up to set email alerts
|

A novel mitogenomic rearrangement for Odorrana schmackeri (Anura: Ranidae) and phylogeny of Ranidae inferred from thirteen mitochondrial protein-coding genes

Abstract: We determined the complete nucleotide sequence of the mitochondrial genome of Odorrana schmackeri (family Ranidae). The O. schmackeri mitogenome (18 302 bp) contained 13 protein-coding genes, 2 rRNA genes, 21 tRNA genes and a single control region (CR). In the new mitogenome, the distinctive feature is the loss of tRNA-His, which could be explained by a hypothesis of gene substitution. The new sequence data was used to assess the phylogenetic relationships among 23 ranid species mostly from China using maximum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 54 publications
0
6
0
Order By: Relevance
“…BI and ML analyses were performed with 59 anuran mt genomes including Pyxicephalus adspersus . In total this included 55 species as the ingroup from Ranidae, Dicroglossidae, Rhacophoridae, Mantellidae, Pyxicephalidae, Petropedetidae, Ptychadenidae, Ceratobatrachidae, and Phrynobatrachidae (Alam et al, 2010; Chen et al, 2011; Hofman et al, 2012; Huang et al, 2016a, 2016b; Jiang et al, 2017; Kakehashi et al, 2013; Kurabayashi et al, 2006, 2010; Li et al, 2014b, 2016b; Lin et al, 2014; Liu, Wang & Zhao, 2017a; Liu et al, 2017b; Liu, Wang & Su, 2005; Ni et al, 2015; Ren et al, 2009; Sano et al, 2004, 2005; Xia et al, 2014; Yan et al, 2016; Yang et al, 2018; Yu, Zhang & Zheng, 2012a; Yu et al, 2012b, 2015; Zhang, Xia & Zeng, 2016; Zhang et al, 2005, 2009, 2013, 2018a; Zhao, Meng & Su, 2018; Zhou et al, 2009) and four species as outgroups from Microhylidae (Chen et al, 2016; Wang et al, 2018; Zhao, Meng & Su, 2018). We used the nucleotide data to assess BI and ML topology to discuss the phylogenetic position of Pyxicephalus .…”
Section: Methodsmentioning
confidence: 99%
“…BI and ML analyses were performed with 59 anuran mt genomes including Pyxicephalus adspersus . In total this included 55 species as the ingroup from Ranidae, Dicroglossidae, Rhacophoridae, Mantellidae, Pyxicephalidae, Petropedetidae, Ptychadenidae, Ceratobatrachidae, and Phrynobatrachidae (Alam et al, 2010; Chen et al, 2011; Hofman et al, 2012; Huang et al, 2016a, 2016b; Jiang et al, 2017; Kakehashi et al, 2013; Kurabayashi et al, 2006, 2010; Li et al, 2014b, 2016b; Lin et al, 2014; Liu, Wang & Zhao, 2017a; Liu et al, 2017b; Liu, Wang & Su, 2005; Ni et al, 2015; Ren et al, 2009; Sano et al, 2004, 2005; Xia et al, 2014; Yan et al, 2016; Yang et al, 2018; Yu, Zhang & Zheng, 2012a; Yu et al, 2012b, 2015; Zhang, Xia & Zeng, 2016; Zhang et al, 2005, 2009, 2013, 2018a; Zhao, Meng & Su, 2018; Zhou et al, 2009) and four species as outgroups from Microhylidae (Chen et al, 2016; Wang et al, 2018; Zhao, Meng & Su, 2018). We used the nucleotide data to assess BI and ML topology to discuss the phylogenetic position of Pyxicephalus .…”
Section: Methodsmentioning
confidence: 99%
“…A 1151 base pairs (bp) fragment of mitochondrial DNA containing the complete mitochondrial NADH dehydrogenase subunit 2 (ND2) gene and two flanking transfer RNA (tRNA) genes was amplified with the primer pair Ile-LND2 (5’-ATAGGGAGACTTATAGGGGTTC-3’) and Asn-HND2 (5’-CTAAGTCATTACGGGATCGAGGCC-3’) designed according to the complete mitochondrial genome of O . schmackeri from Li et al [ 52 ] (GenBank accession no. KJ149452).…”
Section: Methodsmentioning
confidence: 99%
“…So far, combined with the 38 mitochondrial genome sequences in GenBank database, our phylogenetic analyses revealed that the subfamily Dicroglossinae's monophyly was well supported (Li et al., , ; Roelants et al., ; Yuan et al., ). The subfamily Dicroglossinae is the sister clade to the Occidozyginae (Figure ).…”
Section: Resultsmentioning
confidence: 77%
“…In addition, a tandem repeat of tRNA‐Met gene was easy to find in the three Nanorana species, located between the tRNA‐Gln and ND2 genes. Extra tRNA‐Met was also found in Quasipaa boulengeri , Fejervarya cancrivora , Hoplobatrachus rugulosus , Euphlyctis hexadactylus , Limnonectes bannaensis , and Occidozyga martensii (Alam et al., ; Chen et al., ; Li et al., , ; Ren et al., ; Shan, Xia, Zheng, Zou, & Zeng, ; Zhang et al., ). But this phenomenon is different to that seen in Amolops tormotus and other typical vertebrates (Su, Wu, Yan, Cao, & Hu, ).…”
Section: Resultsmentioning
confidence: 97%